Kidney disease in hepatitis B surface antigen-positive children: experience from a centre in south-west Nigeria and a review of the Nigerian literature (2017)
Background: Kidney disease is an important extra-hepatic manifestation of hepatitis B virus (HBV) infection. However, there is paucity of recent literature on kidney disease in children and adolescents with HBV infection from several parts of sub-Saharan Africa including Nigeria. Objective: To review the pattern of kidney disease in hepatitis B surface antigen (HBsAg)-positive children and adolescents seen at a tertiary hospital in south-west Nigeria. Methods: A retrospective study was undertaken of HBsAg-seropositive children with kidney disease managed at University College Hospital, Ibadan, from January 2004 to December 2015. Patients were identified from the paediatric nephrology unit admissions and the renal histology registers. Results: 24 children and adolescents were studied, 17 of whom were male (70.8%), and the median age was 10.0 years (range 3–15). Ten (41.7%) had nephrotic syndrome, five (20.8%) had non-nephrotic glomerulonephritis, five (20.8%) were in end-stage renal disease (ESRD), including a patient with posterior urethral valves, and four had acute kidney injury secondary to acute tubular necrosis. Renal histology was available for 10 patients: nine had nephrotic syndrome associated with minimal change disease in six, focal segmental glomerulosclerosis in two and one had membanoproliferative glomerulonephritis. The patient with non-nephrotic glomerulonephritis had diffuse global sclerosis. Conclusion: The pattern of kidney disease in HBV-positive children demonstrated a predominance of nephrotic syndrome, followed by non-nephrotic glomerulonephritis, ESRD and acute kidney injury. Better diagnostic facilities and treatment are required. Prevention of HBV infection by universal childhood immunisation is the ultimate goal.